The Influence of Linguistic Intelligence in Increasing Students’ Writing Ability Through Neighborhood Walk Strategy - Munir, Fairus Suryani; Kafryawan, Wira (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2024)
This research is aimed at finding out the influence of linguistic intellingence in increasing the students’ writing ability through neighborhood walk strategy. This research used factorial design. The population was the tenth-year students of SMA Negeri 1 Popayato. The sample selected considering linguistic intelligence test which consist of. 40 students from three parallel classes. The data were analyzed by t-test, one way ANOVA and followed by Tukey test. The researcher finding shows that: (1) the achievement of students’ writing who studied through neighborhood walk strategy was different than those are studied through direct instructional strategy, t-test value (9.635>1.685) for the experimental groups and (7.570 > 1.685) for the control groups. (2) there are was an interaction effect between the use of teaching strategy and linguistic intelligence (f-test value is 49.69 > 2.72 with the level of significance of 0.05. (3) the student who had high linguistic intelligence and studied by Neighborhood Walk strategy had higher on the increase of writing achievement than those who had high linguistic intelligence and studied by direct instructional strategy (Q = 25.238), and (4) the student who had low linguistic intelligence and studied by Neighborhood Walk strategy had higher on the increase of writing achievement than those who had low linguistic intelligence and studied by direct instructional strategy (Q = 21.767).